Isotopic fractionation of water and its photolytic products in the atmosphere of Mars - Alday, J; Trokhimovskiy, A; Irwin, PGJ; Wilson, CF; Montmessin, F; Lefévre, F; Fedorova, AA; Belyaev, DA; Olsen, KS; Korablev, O; Vals, M; Rossi, L; et al. (Springer Nature, 2021)
The current Martian atmosphere is about five times more enriched in deuterium than Earth’s, providing direct testimony that Mars hosted vastly more water in its early youth than nowadays. Estimates of the total amount of water lost to space from the current mean D/H value depend on a rigorous appraisal of the relative escape between deuterated and non-deuterated water. Isotopic fractionation of D/H between the lower and the upper atmospheres of Mars has been assumed to be controlled by water condensation and photolysis, although their respective roles in influencing the proportions of atomic D and H populations have remained speculative. Here we report HDO and H2O profiles observed by the Atmospheric Chemistry Suite (ExoMars Trace Gas Orbiter) in orbit around Mars that, once combined with expected photolysis rates, reveal the prevalence of the perihelion season for the formation of atomic H and D at altitudes relevant for escape. In addition, while condensation-induced fractionation is the main driver of variations of D/H in water vapour, the differential photolysis of HDO and H2O is a more important factor in determining the isotopic composition of the dissociation products.